(untitled) (Global Journal of Medical Research, 2025)
The Autism Spectrum Disorder ASD is a neurodivergent condition that affects communication and social behavior requiring understanding and ensuring rights for an inclusive life Despite advances persistent social and occupational challenges are faced by the autistic community The heterogeneity of the spectrum demands a broad understanding not limited to health but including social and educational aspects The lack of understanding of these complexities results in underestimation of autism and inadequate health services This article aims to deepen knowledge about the rights of people with ASD in Brazil emphasizing legal social and educational aspects To this end a literature review on the rights and public health of autistics was conducted The need for training of health professionals and educators to create inclusive environments is highlighted The application of adaptive therapeutic approaches considering the individual complexities of each autistic person is crucial